2019
DOI: 10.1108/pr-03-2017-0092
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying across the globe: a cross-cultural comparison

Abstract: Purpose The purpose of this paper is to analyze cross-national and cross-cultural similarities and differences in perceptions and conceptualizations of workplace bullying among human resource professionals (HRPs). Particular emphasis was given to what kind of behaviors are considered as bullying in different countries and what criteria interviewees use to decide whether a particular behavior is bullying or not. Design/methodology/approach HRPs in 13 different countries/regions (n=199), spanning all continent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 24 publications
7
67
0
4
Order By: Relevance
“…This study's results, based on upper-middle and middle level employees of service sector, prove that positive behavioral intervention can be helpful in eliminating the antisocial behavior such as bullying. This study also fulfills the recommended gap by Salin et al (2019) to investigate the behavioral expression as an underlying mechanism. The underlying processes between the Machiavellianism and bullying behavior is validated through the conditional mediated impact of role ambiguous job demands and self-impression management on the premise of TAT.…”
Section: Discussionsupporting
confidence: 57%
“…This study's results, based on upper-middle and middle level employees of service sector, prove that positive behavioral intervention can be helpful in eliminating the antisocial behavior such as bullying. This study also fulfills the recommended gap by Salin et al (2019) to investigate the behavioral expression as an underlying mechanism. The underlying processes between the Machiavellianism and bullying behavior is validated through the conditional mediated impact of role ambiguous job demands and self-impression management on the premise of TAT.…”
Section: Discussionsupporting
confidence: 57%
“…Differences between three types of conceptual understanding of bullying behavior among social pedagogues mainly follow previous studies in the area of conceptualizing workplace bullying among adults (Escartín et al, 2011;De Wet, 2014;Salin, et al, 2019), showing that bullying against educators by students and by adults was mainly conceptualized as a hierarchical phenomenon, where the aggression took the form of direct professional work-related strategies, whereby the main differentiating features for this two concepts were the manifestations of workplace bullying forms (public personal or destabilization) and…”
Section: Resultsmentioning
confidence: 64%
“…Most adult respondents (parents: Monks & Smith, 2006;Sawyer et al, 2011;Smorti et al, 2003; teachers and parents: Madsen, 1996;Mishna et al, 2006;teachers and staff members: Harger, 2016;Cheng et al, 2011;teachers: Menesini et al, 2002;Mishna et al, 2005;Naylor et al, 2006;Siann et al, 1993) incorporated into their understanding of learner-on-learner bullying the key components of the generally accepted bullying definition, whereby the same tendencies were revealed among adults in the area of defining workplace bullying (Salin et al, 2019;Saunders et al, 2007) and among educators (De Wet, 2010;2019) in the area of teacher-targeted bullying conceptualizations. Also, present results among social pedagogues confirmed the tendency for teachers, parents, school staff members to focus on physical and verbal behaviours when they describe learner-on-learner bullying (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, work-related mobbing such as giving unreasonable deadlines of unmanageable workloads, or assigning meaningless tasks, is more likely to be reported by employees from professional positions compared to non-work related mobbing behaviors such as being ignored (Salin, 2001). It was also shown that in some | 61 occupations and organizations certain negative acts -mostly work related negative behaviors-are expected as part of the culture and may not be considered as mobbing (Archer, 1999;Salin et al, 2018) and physical mobbing was least likely reported type of mobbing (Einarsen & Raknes, 1997). All mentioned studies have supported the idea that various types of mobbing can be perceived and differentiated by employees; however they were not compared in terms of their antecedents and consequences which would help us to develop new interventions for mobbing.…”
Section: Discussionmentioning
confidence: 99%